Introduction: online jihadist magazines - Stuart Macdonald (Critical Studies on Terrorism, 2018)
This is the introduction to a special section of Critical Studies on Terrorism that focuses on online jihadist magazines. The three articles in this section were all co-authored with undergraduate students from Swansea University's College of Law & Criminology as part of a project that combined research, teaching and employability objectives.